2020
DOI: 10.1002/bio.3913
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of citalopram and tadalafil by the second derivative synchronous fluorescence method in biological fluids; application of Box–Behnken optimization design

Abstract: This is the first study focusing solely on that determination of tadalafil in the presence of citalopram as an antidepressant drug. The determination in biological fluids of a co‐administered antidepressant drug and a sexual stimulation drug is a very critical and important step for psychotic and ischaemic heart disease patients, especially in cases of emergency and this requires therapeutic drug monitoring. A sensitive, efficient and rapid assay was selected satisfactorily and applied for simultaneous determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In this study, studies were found for the determination of the selected SSRIs sertraline, citalopram, and fluvoxamine by the RPLC method for the determination of the compounds alone or simultaneously [20][21][22]. In addition, there are few studies on the determination of optimum conditions of compounds with the experimental design method related to this group [23][24][25]. For the qualitative determination of the selected compounds in this study, the optimum chromatographic condition was determined by examining the change in k values depending on the mobile phase pH at the constant column temperature and the organic modifier concentration in the mobile phase.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, studies were found for the determination of the selected SSRIs sertraline, citalopram, and fluvoxamine by the RPLC method for the determination of the compounds alone or simultaneously [20][21][22]. In addition, there are few studies on the determination of optimum conditions of compounds with the experimental design method related to this group [23][24][25]. For the qualitative determination of the selected compounds in this study, the optimum chromatographic condition was determined by examining the change in k values depending on the mobile phase pH at the constant column temperature and the organic modifier concentration in the mobile phase.…”
Section: Introductionmentioning
confidence: 99%
“…For determination of AFH, HPLC [15][16][17][18][19], spectrophotometric [20][21][22][23][24][25], spectrofluorometric [25][26][27][28] and voltammetric [29][30][31] procedures were revealed. For TDF determination, different HPLC [32][33][34], spectrofluorometric [35][36][37][38], spectrophotometric [35,[39][40][41][42] and voltammetric [43][44][45][46] methods were reported for its analytical quantitation.…”
Section: Introductionmentioning
confidence: 99%